The Richer the Better? SES Inequalities In Cause-Specific Adult Mortality In a Long-Term Perspective: Evidence from Sweden 1813-2014 - Debiasi, Enrico; Dribe, Martin (Lund Papers in Economic Demography, 2019)
Higher socioeconomic status (SES) is associated with lower mortality. This has been confirmed using different indicators across several geographical settings. Nevertheless, the mechanisms behind this association are still under debate. In particular, the timing of the emergence of the SES gradient remains an open question. In this paper, we study the development of SES inequalities in cause-specific mortality for a regional population in southern Sweden from the early nineteenth century until 2014. We apply a cause-specific hazard model to estimate mortality differentials by SES. Our results confirm that the SES differences we see today emerged only around 1970. More importantly, our study demonstrates that, with few exceptions, SES differences emerged about the same time for all causes of death. For women it started earlier than for men, particularly in infectious diseases. In the nineteenth and early twentieth century we find a positive association between SES and mortality from circulatory diseases for men. We argue that habits and behaviors embedded in the different social strata played a major role behind the SES differences in mortality that we observe throughout the analyzed period.